Cation-induced fast growth of ultrathin cuprous chloride nanoplatelets. Issue 19 (27th April 2016) - Miao, Zhongzheng; Liang, Minghui; Xiao, Zhichang; Amir, Badshah; Li, Xianglong; Zhi, Linjie
Abstract : Ultrathin cuprous chloride crystalline nanoplatelets have been prepared on a copper surface based on a novel strategy involving a symproportionation reaction. Abstract : A novel strategy involving a symproportionation reaction synergistically mediated by ferric ions and solvent molecules leads to the formation of ultrathin cuprous chloride crystalline nanoplatelets. The thickness of the cuprous chloride nanoplatelets can be about 3 nm, which represents the creation of one new kind of two-dimensional nanomaterial.